Buying and selling laboratory instruments : a practical consulting guide - McMaster, Marvin C. (John Wiley, 2010)
A time-tested, systematic approach to the buying and selling of complex research instruments. Searching for the best laboratory instruments and systems can be a daunting and expensive task. A poorly selected instrument can dramatically affect results produced and indirectly affect research papers, the quality of student training, and an investigator's chances for advancement. Buying and Selling Laboratory Instruments offers the valuable insights of an analytical chemist and consultant with over four decades of experience in locating instruments based upon both need and price.